Al-Faruqi’s Fundamental Ideas and Philosophy of Education - Amir, Ahmad Nabil; Rahman, Tasnim Abdul; Wan Yusof, Wan Sabri; Rashid, Zuriati Mohd (IAIN Samarinda, 2015)
This paper discusses the fundamental ideal and philosophy of education advocated by Ismail Raji al-Faruqi (1921-1986) in realizing the Islamization of knowledge (IOK) project. The concept and perspective of education projected by al-Faruqi was constructed on the worldview of tawhid that reflected the essence and intrinsic philosophy and paradigm of knowledge rooted on Islamic vision of reality and truth. It embodied the comprehensive and holistic vision of education that seeks to integrate the fundamental element of revealed and acquired knowledge. The project envisaged to undertake significant reform in the practice and method of education of the ummah that need to be recast and reproject based on the intrinsic value and paradigm of the Qurâ€™an and its approach to knowledge. This paper will analyse this significant idea and principle and its importance in realizing the IOK vision and reforming the educational system in the Muslim world.Â